Analysis of the Drug-Free Village Program from the Perspective of Progressive Law in Law Enforcement - Jun Mawalidin; Saparwadi; Samsul Hadi (Unram Law Review, 2026)
The Drug Clean Village Program is a program of the National Narcotics Agency of the Republic of Indonesia, which aims to eradicate drug trafficking at all levels of society. The progressivity of drug laws and regulations and the enforcement of community justice have not been comprehensive. So this research aims to determine the direction of the progression of legal justice for all levels of society based on laws and regulations. The type of research used in this study is normative juridical, which focuses on the conceptual approach of legislative rules. The results of this study show that the drug-free village program only looks at the problem, and in fact, the development of laws and regulations and the enforcement of justice needs legal reform.